DIVERSITY, DISTRIBUTION PATTERNS AND COMMUNITY STRUCTURE OF MACROZOOBENTHOS OF DATPUL GAD, A SPRING-FED TRIBUTARY OF NAYAR RIVER, UTTARAKHAND, INDIA - KOTNALA, C. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The present paper deal with macrozoobenthos in the spring-fed stream Datpul Gad which is an important tributary of Nayar River of Garhwal Himalaya. The stream is located in Agroda village of the Pauri district, Uttarakhand. The stream is represented by 14 macrozoobenthic genera namely Caenis, Baetis, Heptagenia, Cinygmula, Ephemerella, Epeorus, Stenopsyche, Chimarra, Philopotamid, Hydropysche, Psephanus, Atherix, Antocha and Perla. The various Physico-chemical parameters of stream viz. water temperature, current velocity, dissolved oxygen, pH, total alkalinity, and total hardness were also studied. The maximum macrozoobenthos were found in the winter season and the least in the monsoon season. The multivariate test of Principal component analysis (PCA) and Canonical correspondence analysis (CCA) were also computed to study the abundance of benthic fauna and their relation with the abiotic factors. The diversity indices such as the Shannon-Wiener diversity index and Margalef index were also calculated to depict the diversity status of benthos in the stream. To represent the similarity of macrozoobenthic taxa of the stream Sorenson similarity index was calculated.